The Vaginal Community State Types Microbiome-Immune Network as Key Factor for Bacterial Vaginosis and Aerobic Vaginitis - De Seta, Francesco; Campisciano, Giuseppina; Zanotta, Nunzia; Ricci, Giuseppe; Comar, Manola (Frontiers in Microbiology, 2019)
Regarding bacterial vaginosis (BV), the relevance of the vaginal microbiota to the women’s health fulfils a key role but knowledge gaps regarding aerobic vaginitis (AV) exist. This study aims to characterize vaginal microbiome and its relationship with the local immune mediators providing an opportunity to define the link between vaginal commensal microorganisms and opportunistic pathogens in the relation of a given vaginal community state type (CST). A total of 90 vaginal samples from Caucasian asymptomatic women of reproductive age (18y–40y) attending the yearly examination and not reporting any vaginal complaints were retrospectively evaluated for microbiome assessment and immune factors dosage. The samples were tested by the Ion Torrent PGM and the Luminex Bio-Plex technologies for the analysis of microbiome and immune factors, respectively. In our study, the CSTs classification together with the local immune response profiling represented a good predictive indicator of the vaginal health suggesting that the predominance of a specific Lactobacillus and its relative abundance are pivotal elements to maintain a physiologic status. Vaginal colonization from Bifidobacterium may absolve a protective role similar to that of Lactobacillus, corresponding to a new identified CST, although studies are needed to better clarify its clinical significance. Moreover, within each CST, a different pattern of inflammation is activated and orchestrated both by the dominant Lactobacillus spp. and by specific non-lactobacillus bacteria, and can give insights into the pathogenic mechanisms. In conclusion, this study contributes to the characterization of vaginal dysbiosis, reshaping this concept by taking into consideration the CST profiling, local immune marker, and immune-microbial network.